Best‐practice pain management in the emergency department: A cluster‐randomised, controlled, intervention trial. (24th November 2015) - Taylor, David McD; Fatovich, Daniel M; Finucci, Daniel P; Furyk, Jeremy; Jin, Sang‐won; Keijzers, Gerben; Macdonald, Stephen PJ; Mitenko, Hugh MA; Richardson, Joanna R; Ting, Joseph YS; Thom, Ogilvie N; Ugoni, Antony M; et al.
Abstract: Objectives: We aimed to provide 'adequate analgesia' (which decreases the pain score by ≥2 and to <4 [0–10 scale]) and determine the effect on patient satisfaction. Methods: We undertook a multicentre, cluster‐randomised, controlled, intervention trial in nine EDs. Patients with moderate pain (pain score of ≥4) were eligible for inclusion. The intervention was a range of educational activities to encourage staff to provide 'adequate analgesia'. It was introduced into five early intervention EDs between the 0 and 6 months time points and at four late intervention EDs between 3 and 6 months. At 0, 3 and 6 months, data were collected on demographics, pain scores, analgesia provided and pain management satisfaction 48 h post‐discharge (6 point scale). Results: Overall, 1317 patients were enrolled. Logistic regression (controlling for site and other confounders) indicated that, between 0 and 3 months, satisfaction increased significantly at the early intervention EDs (OR 2.2, 95% CI 1.5 to 3.4 [ P < 0.01]) but was stable at the control EDs (OR 0.8, 95% CI 0.5 to 1.3 [ P = 0.35]). Pooling of data from all sites indicated that the proportion of patients very satisfied with their pain management increased from 42.9% immediately pre‐intervention to 53.9% after 3 months of intervention (difference in proportions 11.0%, 95% CI 4.2 to 17.8 [ P = 0.001]). Logistic regression of all data indicated that 'adequate analgesia' was significantly associated with patient satisfaction (OR 1.4, 95% CI 1.1 to 1.8 [ P < 0.01]). Conclusions: The 'adequate analgesia' intervention significantly improved patient satisfaction. It provides a simple and efficient target in the pursuit of best‐practice ED pain management.